Noise and psychosocial risk factors of anxiety and work absenteeism among industrial workers in Selangor - Rasdi, Irniza; M., Nor Sharmimi; Zainal Abidin, Emilia (Community Health Society Malaysia (CHSM), 2015)
Background: Industrial workers were found to be psychologically affected by noise exposure at their workplace. However, how noise and psychological state of workers affect their work behaviour is remained unclear. This study aims to determine the relationship between noise exposure and anxiety with work absenteeism among industrial workers. Materials and Methods: This cross-sectional study involved 80 industrial workers who were exposed to occupational noise in a manufacturing company in Bangi, Selangor. Ambient noise levels were measured by using sound level meter and personal noise exposure were measured by noise dosimeter. A set of questionnaire consisted of COSPOQ and HPQ were used to measure anxiety level and work absenteeism respectively. Result: Noise exposure levels were above the permissible exposure limits but it was not significant in predicting anxiety levels and work absenteeism. These findings indicated that those who were married had higher level of anxiety than those who were single. Those who perceived more clarity in their role had lower level of anxiety than those who perceived that their role was unclear. Only marital status was significant in predicting work absenteeism. Conclusion: Findings indicated that marital status influenced anxiety and work absenteeism. Hence, creating a work environment which is friendlier to working parents will potentially improve workers’ mental health and their work behaviour. Improving the clarity of duties may further enhance their well-being.